Corporate governance guideline relevance to Maltese family public interest companies a small state perspective - Baldacchino, Peter (Array, 2020)
The objectives of this paper are to investigate the relevance of guidelines on good corporate governance (CG) to family public interest companies (PICs) within the small state of Malta and to recommend how existing guidelines may be improved and tailored for such companies. An explanatory mixed-methods empirical approach is adopted with a structured questionnaire being first administered to 17 respondents in 12 PICs owned by different families. This was then followed by semi-structured interviews with the representatives of 11 of these PICs. Findings indicate that there is a need for the existing guidelines to be improved for them to become more in line with the needs of PICs which are characterised by dominant family interests. In this respect, this paper recommends possible principles and guidelines that may be used by the relevant authorities either to improve the existing PIC guidelines or to issue a new set of guidelines aimed specifically for family PICs. Given the peculiarities of such companies, it is clear that the guidelines have to contain elements that address the CG structure, such as the need to formally document a family governance plan. Clearer guidance is needed on the appointment and composition of the Board of Directors, on the employment, conduct, compensation and performance evaluation of managers, as well as on the composition of the ownership of family PICs. Additionally, the paper concludes that a relevant factor for family PICs in carrying out improvements to their CG is that they continue to place more importance than other PICs to their continued existence.